The spatial dimension of internal labormarkets - Tavares, Marisa (2018)
We integrate into a unified framework the spatial and the employment dimensions of worker mobility, tracing workers across firms, across establishments, and across regions. Drawing upon the spatial dimension of internal labor markets in firms with multiple establishments in multiple locations, our results indicate that the contemporaneous wage premium to migration is around 3 percentage points. For the case of job switchers, we find that the return to regional migration is due to access to better jobs at the destination. We also document the existence of an urban premium for same‐employer migrants but for employer changes this premium is driven by selection.